From Shakespeare to Obama - Hart, J. author. aut Link
XV, 255 p.
Keywords: From Shakespeare to Obama discusses language, slavery, and place from the Portuguese enslavement of African people, through slavery in Shakespeare's plays, to President Obama's 2012 speech on "modern slavery." Balancing close reading with context, this expansive book offers new insight into questions of otherness, rhetoric, and stereotyping.